Non-Coding RNAs in Transcriptional Regulation. - Chen, Y.A.; Aravin, A.A. (Current molecular biology reports., 2015)
Transcriptional gene silencing guided by small RNAs is a process conserved from protozoa to mammals. Small RNAs loaded into Argonaute family proteins direct repressive histone modifications or DNA cytosine methylation to homologous regions of the genome. Small RNA-mediated transcriptional silencing is required for many biological processes, including repression of transposable elements, maintaining the genome stability/integrity, and epigenetic inheritance of gene expression. Here we will summarize the current knowledge about small RNA biogenesis and mechanisms of transcriptional regulation in plants, Drosophila, C. elegans and mice. Furthermore, a rapidly growing number long non-coding RNAs (lncRNAs) have been implicated as important players in transcription regulation. We will discuss current models for long non-coding RNA-mediated gene regulation.